Irrigação com efluente tratado de abatedouro de aves sobre o solo e a produção florestal - Araujo, Izabela Regina Costa (2019)
The application of treated wastewater on soil is one of the main forms to final disposal and can be considered a post-treatment. Although planted forests generally have good tolerance to effluent disposal, but, the effects of this provision on forest and soil responses should be evaluated. In this way, the aim of this work was to evaluate, over two years, the effects of drip irrigation with treated effluent from a poultry slaughterhouse, at different rates, on the soil and on the forest. Sixteen plots were implanted in eucalyptus forest areas, four treatments (irrigation rates of 0, 100, 200 and 300 m³ha-1dia-1) and 4 replications for each treatment. Soil samples were evaluated in relation about it fertility and forest by it growth and production variables. The main results were the best fit, hyperbolic and Naslünd hypsometric models, with a average standard error of 0.6 m and the Dissescu-Meyer volumetric model, with an average standard error of 0.017 m³. A positive and significant correlation was observed between the annual average increment and the rates of application of effluents tested. The treatments had significant effects for diameter at breast height, individual basal area, basal area per hectare, individual volume and volume per hectare. The irrigation rate of 300 m³ha-1dia-1 produced the highest averages for all these variables. At this irrigation rate, was observed an average annual increment (AAI) 92% higher than the control. In addition, irrigation rates influenced soil phosphorus and potassium concentrations at 24 months of irrigation. The irrigation rate of 300 m³ha-1dia-1 was the one with the highest concentrations of this nutrient. There was a relation between the dominant height of the trees and the concentrations of organic matter and pH of the soil, and negative with calcium and potassium. The diameter at breast height correlates positively with iron and copper concentrations and negatively with zinc and manganese.